(untitled) (Baghdad Science Journal, 2018)
Bacopa monnieri L. (Scrophulariaceae), synoname is Herpestis monniera that provides bioactive compounds, especially triterpenoid saponins (Bacosides) which exhibits an important biological activities, like hypothyroidism, anticonvulsant, memory enhancing and antistress. Because there are no researches about B. monnieri L. plant that grow in Iraq, and there active compounds especially triterpenoid saponin (TS), and there effects. This study was detected the presence of (TS) in, and examined the cytotoxic and the antioxidant activity of these compounds in vitro. The study was included the extraction and identification of TS from the whole parts of B. monnieri L. by using three methods, and the best yield was analyzed by High Performance Liquid Chromatographic (HPLC) to identify bacosides compounds. In vitro, TS was examined the cytotoxic activity against two cancer cell lines, human cervical cancer (Hela), rhabdomyo sarcoma (RD), and rat embryogenic fibroblast (REF) as a normal cell, at concentrations of 62.5, 125, 250, 500 and 1000 ?g/ml at 24, 48, and 72-hr. Free radical 1,1Dyphenyl-2-picrylhydrazyl radical (DPPH) was used for testing the ability of the TS as antioxidant at 20, 40, 60, 80, 100 ?g/ml concentrations. The results revealed that B. monnieri plant had many components of bacosides when detected by HPLC. Cytotoxic study suggested that TS inhibited the growth of cancer cells, and this effect is depending on the extraction of TS concentration. The effect of TS on Hela cell line was more than that for RD, while the highest effect of TS on Hela was at the concentration of 250 ?g/ml after 48 hr. The cytotoxic effect has a significant effect at (P?0.05). The results revealed that TS has high antioxidant influence 99.37% at 100 ?g/ml concentrations, followed by 98.20% in 80 ?g/ml concentration.